Reformation Government and Role Political Law in Forming Public Policy - Hotman Manullang; Tamaulina Br. Sembiring; Ismidar Ismidar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Studies This investigate connection between change order manage And strength law-politics Which to form policy public. Studies This explore influence from change governance the current government in progress to design and implementation policy public with background behind reform order manage moment This . For analyze various subject, study This use study qualitative with analysis document And study literature in a way comprehensive. Framework theoretical in study This covers knowledge about governance changes, which include various models and their impacts. At the same time, the idea about dynamics law-politics investigated , highlighted How problem law interact with process political For to form results policy public. Study This to study world post reform through thorough data analysis, analyzing change policy public and its performance. Research This Also to study role component law-politics in making policy, highlighting contribution, obstacle, and the problems that faced. Findings This highlight existence relatedness between reform government And strength legal-political, so that give outlook about landscape policy the public who are developing. Study This add better understanding Good about impact governance changes and complex processes involvement law-politics in development policy public. The maker policy will get benefit from consequence This , Which will give outlook important for order manage And formation more policies effective . The proposal emphasize areas that need achieved in reform future governance and consolidation not quite enough answer law-politics in evolution policy public Which currently ongoing.